Altered developmental programs and oriented cell divisions lead to bulky bones during salamander limb regeneration - Kaucka, Marketa; Joven Araus, Alberto; Tesarova, Marketa; Currie, Joshua D; Boström, Johan; Kavkova, Michaela; Petersen, Julian; Yao, Zeyu; Bouchnita, Anass; Hellander, Andreas; Zikmund, Tomas; Elewa, Ahmed; et al. (Nature communications, 2022)
There are major differences in duration and scale at which limb development and regeneration proceed, raising the question to what extent regeneration is a recapitulation of development. We address this by analyzing skeletal elements using a combination of micro-CT imaging, molecular profiling and clonal cell tracing. We find that, in contrast to development, regenerative skeletal growth is accomplished based entirely on cartilage expansion prior to ossification, not limiting the transversal cartilage expansion and resulting in bulkier skeletal parts. The oriented extension of salamander cartilage and bone appear similar to the development of basicranial synchondroses in mammals, as we found no evidence for cartilage stem cell niches or growth plate-like structures during neither development nor regeneration. Both regenerative and developmental ossification in salamanders start from the cortical bone and proceeds inwards, showing the diversity of schemes for the synchrony of cortical and endochondral ossification among vertebrates.
Keywords: Osteogenesis; Bone and Bones; buněčné dělení; Urodela; kosti a kostní tkáň; osteogeneze; zvířata; Cell Division; Mammals; Cartilage; savci; Caudata; chrupavka; Animals